2015
DOI: 10.22514/sv101.042015.8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of neurological outcome in the emergency department for elderly patients following out-of-hospital restoration of spontaneous circulation

Abstract: Aims. Survival rates for cardiac arrest in acute medicine are higher following outof-hospital restoration of spontaneous circulation (OH-ROSC). However, data pertaining to OH-ROSC is limited in the elderly population. We aimed to assess the predictors of neurological outcome among elderly patients with OH-ROSC.Methods. We retrospectively analyzed the data of patients 65 years and older who achieved OH-ROSC and who presented to the emergency department (ED) between 2009 and 2013. The following parameters were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The remaining 7 observational studies only evaluated a single lactate concentration shortly after ROSC 69,77–82 . Four of the 7 studies used multivariate analyses including blood lactate concentration in addition to other potentially prognostic factors and showed an independent association between lactate concentration and favorable neurologic outcome 69,78,81,82 .…”
Section: Measurement Of Electrolytes and Other Blood Chemistry Compon...mentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 7 observational studies only evaluated a single lactate concentration shortly after ROSC 69,77–82 . Four of the 7 studies used multivariate analyses including blood lactate concentration in addition to other potentially prognostic factors and showed an independent association between lactate concentration and favorable neurologic outcome 69,78,81,82 .…”
Section: Measurement Of Electrolytes and Other Blood Chemistry Compon...mentioning
confidence: 99%
“…Four of the 7 studies used multivariate analyses including blood lactate concentration in addition to other potentially prognostic factors and showed an independent association between lactate concentration and favorable neurologic outcome 69,78,81,82 . One of the 7 studies was a retrospective evaluation of 55 elderly people who achieved prehospital ROSC and used receiver operating characteristic curve analysis to identify a cutoff admission lactate concentration of 7.8 mmol/L (70 mg/dL), which had a sensitivity of 90.5% and a specificity of 55.9% to predict favorable neurologic outcome 79 . The other 2 studies found no association between admission lactate and favorable neurologic outcome in adult people with OHCPA 77,80 …”
Section: Measurement Of Electrolytes and Other Blood Chemistry Compon...mentioning
confidence: 99%